1988
DOI: 10.1136/ard.47.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer in rheumatoid arthritis.

Abstract: GlasgowSUMMARY In a study of patients attending a rheumatology clinic 230 unselected patients, 185 with rheumatoid arthritis (RA) and 45 with other rheumatic disorders (non-RA), were examined by endoscopy and a detailed history of symptoms referable to the gastrointestinal tract was taken. A peptic ulcer was found in 67 (36%) of the patients and in 13 (29%) of the non-RA group. Gastric ulceration was more common in the group with RA (32 patients (17%) compared with three patients (7%) in the non-RA group); 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…The suggestion that patients with rheumatoid arthritis are more prone to gastric ulceration has been much dis cussed but it is not supported by clinical evi dence. Some studies in rheumatoid arthritis patients have found an excess of GUs [23][24][25], others have not [28] and some have found a large excess of GUs in the control group of osteoarthritis patients taking NSAIDs [27] -suggesting that the drugs themselves rather than the disease are of pri mary importance.…”
Section: Identifying At-risk Groupsmentioning
confidence: 99%
“…The suggestion that patients with rheumatoid arthritis are more prone to gastric ulceration has been much dis cussed but it is not supported by clinical evi dence. Some studies in rheumatoid arthritis patients have found an excess of GUs [23][24][25], others have not [28] and some have found a large excess of GUs in the control group of osteoarthritis patients taking NSAIDs [27] -suggesting that the drugs themselves rather than the disease are of pri mary importance.…”
Section: Identifying At-risk Groupsmentioning
confidence: 99%
“…Prospective cohort studies suggest a 50% enhancement (Beard et al, 1987;Carson et al, 1987). Case control studies place the relative risk at between three and five (Armstrong & Blower, 1987;Faulkner et al, 1988& Somerville et al, 1986, whilst uncontrolled endoscopic studies have suggested a much greater risk (Collins & du Toit, 1987;Farah et al, 1988;Larkai et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulceration has been demonstrated by endoscopy in 80 of 230 unselected patients receiving regular NSAID treatment. 5 In one prospective endoscopic study NSAID treatment resulted in a 50% incidence of ulceration and mucosal inflammation.6 Non-steroidal anti-inflammatory drug induced gut lesions lead to significant morbidity through dyspepsia, bleeding and perforation, and can lead to an appreciable rate of death.7 8 Such lesions may often be asymptomatic. 9 If the withdrawal of the NSAID is impractical for a particular patient, the prevention of NSAID induced gut lesions assumes additional importance.…”
Section: Discussionmentioning
confidence: 99%